Tooth eruption and obesity in 12-year-old children - Hai Ming Wong; Si-Min Peng; Yanqi Yang; Nigel Martyn King; Colman Patrick Joseph McGrath (Elsevier, 2017)
Background/purpose: There is a need to comprehensively investigate the relationship between tooth eruption and obesity. The study aimed to investigate the relationship between erupted permanent tooth number and obesity among 12-year-old children in a population-based study. Materials and methods: A random sample of 806 12-year-old schoolchildren in Hong Kong was recruited. Oral examinations were conducted and the eruption status of the permanent teeth was assessed. Body height, body weight, waist circumference (WC), hip circumference, and triceps skinfold thickness (TRSKF) were measured to assess the adiposity statuses [weight-height ratio (W/H) and body mass index (BMI) for general obesity; WC and waist-hip ratio (WHR) for central obesity; and TRSKF for peripheral obesity]. The relationships between erupted permanent tooth number and adiposity statuses were examined in bivariate analysis and analysis of covariance. Results: The response rate was 82.9% (n = 668/806). Three hundred and forty-six (50.9%) children had 28 teeth erupted. Second molars had the highest rate of noneruption (17.5-35.8%). The mean number and standard deviation (SD) of erupted permanent tooth were 26.4 (2.4). The mean value and SD were 31.1 (6.3) for W/H, 19.8 (3.7) for BMI, 70.4 (9.4) for WC, 0.82 (0.06) for WHR, and 11.8 (4.5) for TRSKF, respectively. After accounting for sociodemographic factors, analysis of covariance identified that W/H, BMI, WC, and WHR were positively associated with the number of erupted permanent teeth (P < 0.01). Conclusion: Erupted permanent tooth number was positively associated with obesity (general and central) among a population-based sample of 12-year-old children in Hong Kong.